2019
DOI: 10.3390/f10050460
|View full text |Cite
|
Sign up to set email alerts
|

Genome Size Variation within Species of Chinese Jujube (Ziziphus jujuba Mill.) and Its Wild Ancestor Sour Jujube (Z. acidojujuba Cheng et Liu)

Abstract: One of the most important attributes of a genome is genome size, which can to a large extent reflect the evolutionary history and diversity of a plant species. However, studies on genome size diversity within a species are still very limited. This study aims to clarify the variation in genome sizes of Chinese jujube and sour jujube, and to characterize if there exists an association between genome sizes and geographical variation. We measured the genome sizes of 301 cultivars of Chinese jujube and 81 genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…For a long time, the taxonomic status of jujube and sour-jujube has been controversial ( Li et al, 2018 ; Wang et al, 2019 ; Liu M. et al, 2020 ). To address these questions, many studies have been carried using molecular markers to analyze the nuclear genome, including those focusing on the haplotype composition, genetic diversity, and geographical origin of jujube ( Liu et al, 2014 ; Shen et al, 2020 ; Song et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, the taxonomic status of jujube and sour-jujube has been controversial ( Li et al, 2018 ; Wang et al, 2019 ; Liu M. et al, 2020 ). To address these questions, many studies have been carried using molecular markers to analyze the nuclear genome, including those focusing on the haplotype composition, genetic diversity, and geographical origin of jujube ( Liu et al, 2014 ; Shen et al, 2020 ; Song et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the genomic information on Ziziphus species is related to Z. jujuba, for which the entire genome has been sequenced (Huang et al, 2017;Liu et al, 2014). Genome size variation within two diploid Ziziphus species, Z. jujuba [(2n = 2x = 24) and Z. acidojujuba (2n = 2x = 24)], was reported recently (Wang et al, 2019) (Wang et al, 2019). Factors that can affect plant nuclear DNA include the internal standard used and environmental conditions, so a more comprehensive investigation involving a more diverse Z. mauritiana collection of germplasms consisting of both cultivars, and wild species of all ploidy levels from Asia and Africa, and growing under the same conditions is necessary to assess the extent of this intraspecific variation.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular tools, including amplified length polymorphism (Singh et al, 2006) and simple sequence repeat (Liang et al, 2019), have been used to assess the genetic diversity of Z. mauritiana accessions, but these studies were generally limited to Asian germplasms. In addition, reports on nuclear DNA content analyses have been published, but these studies were mostly done on Z. jujuba and its wild ancestor, the sour jujube, Z. acidojujuba (Wang et al, 2019). Wu et al (2013) reported a nuclear DNA content of 0.40 to 0.44 pg C-DNA (393.6-429.6 Mb) for Z. jujuba, depending on the cultivar, and 0.45 pg C-DNA for Z. acidojujuba.…”
mentioning
confidence: 99%
“…Some studies predicted that genome size variation could be changing together with fruit size, similar to ploidy levels [12,31,32]. The obtained data were evaluated as possible correlations between relative genome size and pomological traits.…”
Section: Discussionmentioning
confidence: 99%